Investigation faculty of education students' cyberloafing behaviors in terms of various variables - Arabaci, İ. Bakır (Sakarya University, 2017)
Today, internet-based information technologies are sine qua non of effective learning and teaching. By the use of multiple multi-media tools in education, learning environment is enriched, persistence of learning is ensured and the boringness of the course is prevented. However, the purposeless use of internet in classrooms leads students to get disconnected from the course and become distracted, the prevention of motivation, and discipline problems.In particular, the facts that smart mobile phones have become widespread and students come to classroom with their mobile phones can lead to the spread of cyberloafing behaviors during courses. The cyberloafing behaviors in education refer to the fact that students use the internet within course hours for the things irrelevant to course. This research aims to investigate the states of showing cyberloafing behaviors in these courses of the faculty of education students taking Computer I and II courses. The students taking computer I and II courses in different departments of Fırat University Faculty of Education and 1st and 4th grade students in the Computer Instructional Technologies (CIT) department constitute the study population of the research. According to research findings, although students stated that the idea of being engaged in cyberloafing during the course cannot be accepted, it was concluded that they followed their e-mail, participated in discussion groups, and that further cyberloafing behaviors were shown by male students in terms of gender variable, the students in the upper class in terms of class variable, the students who are experts in using the internet, those with more internet seniority and those with personal computers. © The Turkish Online Journal of Educational Technology.
Keywords: Computer laboratory; Cyberloafing behavior; Faculty of education students; Social networks